EFIKASI DIRI MATEMATIKA DAN HUBUNGAN DENGAN TEMAN SEBAYA SEBAGAI PREDIKTOR PRESTASI BELAJAR MATEMATIKA - , ANIQ HUDIYAH BIL HAQ; , Prof. Dr. Asmadi Alsa, SU. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Human resources who created from well education make human who can compete in necessity era, for knowing human who have good resources such as their achievement. This research based on less of Mathematics achievement of Senior High School Students in Indonesia, whereas mathematics is important subject in development of communication and information technology, therefore this aim research to analyze and investigate Mathematics achievement on Senior High School students are observed base on Mathematics selfefficacy and peer relationship. This research is conducted use quantitative approach with regression analysis. Subjects who used are 143 Students of Senior High School in Surakarta which measurement of their Mathematics achievement use cognitive final marks on report of odd semester of academic year 2013/2014. Variables of Mathematics self-efficacy and peer relationship are measured use scale. Based on data analysis results, are obtained conclusion that Mathematics self-efficacy and peer relationship both can predict Mathematics achievement.